Gambaran Literasi Awal Siswa Kelas Rendah Sekolah Dasar terhadap Penggunaan Media Ajar Menyusun Huruf - Dela Puspita; Jesi Alexander Alim; Zakiah Ulya (CV. Aksara Global, 2025)
This study aims to describe the early literacy skills of elementary school students through the use of letter-arranging teaching media based on three main indicators: letter suitability, accuracy in arranging letters into words, and accuracy in combining syllables into words. Early literacy is a crucial foundation for mastering reading and writing skills that influence students’ academic development. However, many lower-grade students still face difficulties in recognizing letters and forming words correctly. To address this, learning media that are concrete, interactive, and suitable for children’s developmental stages are needed. The letter-arranging teaching medium was chosen because it trains basic reading skills through enjoyable play-based activities. This research employed a descriptive quantitative method involving 22 second-grade students. Data were collected using a Likert-scale questionnaire consisting of 10 statements, then analyzed using the mean score and response distribution. The results showed an overall mean of 3.39, categorized as very good. The highest indicator was letter suitability and accuracy in forming simple words (mean 3.6), while the lowest was accuracy in combining syllables into complex words (mean 3.1). These findings indicate that the letter-arranging medium effectively strengthens early literacy, particularly in letter recognition and simple word composition, while also improving motivation, confidence, and cooperation.